Thick Individuality Within Thin Sense of Public Confusion within the Battle Against Corruption - SANTOSO, PURWO (Jurnal Studi Pemerintahan, 2013)
Various concepts, models or theoretical frameworksare on offer, to frame the public in fighting againstcorruption in Indonesia. They include: bureaucraticreform, good governance, civil society engagementetc. In response to the failure to bring corruptionfreestatus, experts unnoticeably tend to blame publicofficers instead of ensuring the accuracy and thereliability of the framework. This reflective literaturereview reveals such tendency. To begin with, it mapsout the logical basis of each approach, particularlyin conceptualizing the ‘public’, the ‘private’, andtheir relationship. The reliability of the approacheswill emerge as we link the conceptualization withreal life the public or socio-cultural context. The reviewreveals that analysis on corruption and its imperativeare ideologically driven, and hence, suffersfrom ideological bias. It obsesses with altering thebehaviour of public officers, which inevitably entrappedwith particular set-up. As liberal discoursetake place in non-liberal institutional set-up, thepublic fail to comprehend the nature of the problemsand the solution on offer. Instead of setting upcontext-specific agenda, public a dragged on variousforms of reform such as granting political rights,enhancing civil society, articulate more autonomyand alike. As overwhelming individual within thebattles against corruption overloaded with assertingof more public role, they encountered with difficultyin setting the boundary between the public and theprivate. As Indonesia has been endowed with differentinstitutional set-up in governing public affairs,corruption-free public governance remains elusive.This is because the reforms dismantle the existing powerbase, which actually is vital for winning the fight against corruptivesystemKEYWORDS: public, private, corruption